Food addiction and impaired executive functions in women with obesity - Steward, Trevor; Mestre‐Bach, Gemma; Vintró‐Alcaraz, Cristina; Lozano‐Madrid, María; Agüera, Zaida; Fernández‐Formoso, José A.; Granero, Roser; Jiménez‐Murcia, Susana; Vilarrasa, Nuria; García‐Ruiz‐de‐Gordejuela, Amador; Veciana de las Heras, Misericordia; Custal, Nuria; et al. (European eating disorders review, 2018)
Background Individuals with obesity (OB) often report suffering from addiction‐like symptoms. As in addictions, deficits in executive function domains, such as decision‐making and sustained attention, are found in OB. No study to date has examined the associations between food addiction, OB, and neuropsychological performance. Method Thirty‐three adult women with OB and 36 healthy weight controls completed the Yale Food Addiction Scale Version 2.0, a validated instrument used to assess food‐related addictive behaviours. Additionally, participants completed computerized versions of the Iowa Gambling Task (IGT) and Conners' Continuous Performance Test, second edition (CPT‐II) to examine decision‐making and attentional control, respectively. Results Food addiction criteria were met in 24.2% of the participants with OB and in 2.8% of the control group. In the OB group, food addiction severity levels were negatively correlated with overall scores on the IGT. Participants with OB meeting criteria for food addiction committed more omissions and perseveration errors on the CPT‐II compared with those without food addiction. Conclusions Our results point to an association between food addiction severity levels and impairments in decision‐making and attentional capacity in individuals with OB. Given the heterogeneity found in OB, it stands to reason that this subset of patients with food addiction could potentially benefit from interventions targeting neuropsychological deficits.